Nível de atividade física de escolares do ensino médio: estudo sobre a associação com o desempenho acadêmico e a percepção de barreiras à prática de atividades físicas - Pandolfo, Kelly Christine Maccarini (2015)
The objective of this study was to investigate the relationship between physical activity level (PAL) and academic performance (AP) of high school students from a public school, as well as identify perceived barriers (PB) to physical activity. The participants were 348 adolescents aged between 14 and 19 years, who attended a federal public school, with military characteristics. For information regarding the PAL, the International Activity Questionnaire (IPAQ), short version was used. The AP was obtained through the average scores of the first semester of 2015, within the three major Knowledge Areas, as defined by the National Curriculum Standards. To investigate the perceived barriers, an instrument consisting of 12 statements was used. All the instruments used were validated for adolescents. Data collection was carried out in June/2015, in the last week of school before the schools break, during physical education class. The data from AP of each student were obtained after school recess (July/2015), after academic ratings of the first semester were computed. Descriptive data analysis was used to characterize the study population and to analyze PB. We analyzed the data distribution curve through the Kolmogorov-Smirnov test and afterwards, the Spearman correlation test was used in the analysis of relations between the PAL, AP and PB. The Mann Whitney test was applied to verify the possible differences between the average grades of Knowledge Areas between active and insufficiently active students and also for differences between sexes` PB. With the Kruskal Wallis test, the possible differences in the PB between high school years were checked. The chi-square test was used to compare proportions for the analysis of individual barriers between the sexes. 58.6% of the students were considered active and there was no significant correlation between the AP and the PAL. Higher minimal grades were observed in active students and higher average grades for areas 1 and 2 among the participants of sports teams (p = 0.017; p = 0.014). The most prevalent PB for physical activity were: I have many tasks, lack of time and the weather makes it difficult to practice. Girls reported more PB and greater frequency of answers in all BP investigated. Significant correlation was found (r = -0.3290, p <0.0001) between PAL and PB. In conclusion, PAL had no negative effect on AP and participants of sports teams achieved better AP, demonstrating that sports activities can cause beneficial effects on cognitive performance. As for the perception of barriers, these can negatively impact the adoption of a physically active lifestyle, since the greater the number of BP, the lower was the PAL of the studied adolescents.